Optimization of asphalt mixture design based on the compressible packing model - Muhadeer, Yeermulati; Liang, Sun; Peiwen, Hao; Ningbo, Li; Junbiao, Wang (Frontiers in Materials, 2023)
This paper first put forward a modified compressible packing model. The filling characteristic of coarse aggregate was studied. The different matrix compaction indexes η and compaction indexes K are selected to study the influence of modified compressible model on the pavement performance. Besides the design methods based on the 4% air void and minimum voids in mineral aggregate are compared through the volume parameters and pavement performance based on the modified compressible model. The asphalt mixture performance with three gradations were analyzed. The test results show that as the matrix compaction index η decreases, optimum asphalt content of the both two methods are all increases, while the VMA decreases.. Finally, the optimized asphalt mixture design method based on the compressible packing model was proposed, which shows a good application prospect.